GC-MS analysis of three Diospyros species and evaluation of its in vitro rat intestinal a-glucosidase and FRAP activity - NOVA ALFIAN HARIYANTO; RICO RAMADHAN; YANUARDI RAHARJO; YAZDANIYAR FAJRI HALIMI FIRDAUS; IRMAYANTI TRI KURNIA; DINDA AYU LESTARI; SUHARTINI SUWANDARI; NUR FARIHA MAHMUDA; JOURDHAM NATHANAEL; KIETTIPUM PHONTREE; PREECHA PHUWAPRAISIRISAN; LUKMAN RIYADI; ARRIZAL RAHMAN; NURLITA ABDULGANI (Society for Indonesian Biodiversity, 2024)
Abstract. Hariyanto NA, Ramadhan R, Raharjo Y, Firdaus YFH, Kurnia IT, Lestari DA, Suwandari S, Mahmuda NF, Nathanael J, Phontree K, Phuwapraisirisan P, Riyadi L, Rahman A, Abdulgani N. 2024. GC-MS analysis of three Diospyros species and evaluation of its in vitro rat intestinal a-glucosidase and FRAP activity. Biodiversitas 25: 2442-2453. The vast diversity of natural products has long been recognized as a potentially valuable source of bioactive compounds derived from nature. The Diospyros species, belonging to the Ebenaceae family, thrive in tropical forest regions and have been traditionally used for treating various disorders such as ischemic stroke, hypertension, and infectious diseases. This research aims to assess the phytochemical constituents, rat intestinal a-glucosidase, and Ferric-Reducing Antioxidant Power (FRAP) of non-polar (n-hexane) and semi-polar (dichloromethane) extracts from three Diospyros species, i.e., Diospyros buxifolia (Blume) Hiern; Diospyros celebica Bakh.; Diospyros confertiflora (Hiern) Bakh). Gas Chromatography-Mass Spectrometry (GC-MS) analysis identified numerous bioactive secondary metabolites in the extracts. The study revealed that the semi-polar extracts of D. buxifolia exhibited potent rat intestinal a-glucosidase inhibitory activities, with an IC50 value of 33.31±3.23 ug/mL. The IC50 of acarbose as a positive control was 6.31±0.31 ug/mL. The FRAP test demonstrated that the non-polar and semi-polar leaf extracts of the three Diospyros species from East Kalimantan are potential sources of natural antioxidants, with the IC50 in the range of 6.48±0.38 umol Fe/g - 11.35±0.16 umol Fe/g. The results of this study confirm the therapeutic properties of leaf extracts derived from 3 Diospyros species, which align with their traditional medicinal use.